Epigarcinol and isogarcinol isolated from the root of Garcinia ovalifolia induce apoptosis of human promyelocytic leukemia (HL-60 cells). (December 2015) - Pieme, Constant; Ambassa, Pathaleon; Yankep, Emmanuel; Saxena, Ajit
Abstract Background Plants from garcinia genus have been used for centuries against several diseases. Objective This study aimed to investigate the mechanism of apoptosis induced by epigarcinol and isogarcinol isolated from the root ofGarcinia ovalifolia (Clusiaceae) on human promyelocytic leukemia (HL-60 cells). Methods Epigarcinol and isogarcinol were isolated from the root ofG. ovalifolia by using column chromatography method. The antiproliferative property of these molecules and fractions were assessed with 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. The light fluorescence microscope was utilized to observe the morphological changes of HL-60 cells after 24 h treatment. Early apoptosis and cell cycle distribution were analyzed by using flow cytometry (FCM). Results The results showed that epigarcinol and isogarcinol inhibited the proliferation of HL-60 and PC-3 cells in a concentration-dependent manner with IC50 varying between 4 and 76 µg/mL depending on the cell line and the molecule. The apoptosis rate and the number of apoptotic cells significantly increased with the augmentation of the concentration of the molecules. The results of flow cytometry (FCM) indicated that epigarcinol and isogarcinol induced significant G2 /S arrest of HL-60 cells, the disruption of mitochondrial membrane potential and reactive oxygen species (ROS) generation. Conclusion These results indicated that epigarcinol and isogarcinol demonstrated in vitro antiproliferative properties and induce apoptosis of HL-60 cells which is related to the G2 /S arrest, and it exerts its apoptotic effect through the loosing of mitochondrial membrane potential.